Architectures of festival in early modern Europe
1 online resource
Keywords: "This fourth volume in the European Festival Studies, 1450-1700 series breaks with precedent in stemming from a joint conference (Venice, 2013) between the Society for European Festivals Research and the PALATIUM project supported by the European Science Foundation. The volume draws on up-to-date research by a Europe-wide group of academic scholars and museum and gallery curators to provide a unique, intellectually-stimulating and beautifully-illustrated account of temporary architecture created for festivals of the sixteenth and seventeenth centuries, together with permanent architecture pressed into service for festival occasions across major European locations including Italian, French, Austrian, Scottish and German. Appealing and vigorous in style, the essays look towards classical sources while evoking political and practical circumstances and intellectual concerns--from re-shaping and re-conceptualizing early sixteenth-century Rome, through providing for the well-being and political allegiance of Medici-era Florentines and exploring the teasing aesthetics of performance at Versailles to accommodating players and spectators in seventeenth-century Paris and at royal and ducal events for the Habsburg, French and English crowns. The volume is unique in its field in the diversity of its topics and the range of its scholarship and fascinating in its account of the intellectual and political life of Early Modern Europe."--Provided by publisher.